HELMINTH FAUNA OF MYOMORH RODENTS (RODENTIA, MYOMORHA) IN THE CENTRAL CHERNOZEM STATE NATURE RESERVE - E. A. Vlasov; N. S. Malisheva; A. V. Krivopalov (Российский паразитологический журнал, 2016)
Objective of research. Helminth fauna of rodents was investigated in the Central Chernozem State Nature Reserve (Kursk Region, Russia) in 2012-2014. Results and discussion. In total 499 individuals of twelve species from four families of rodents were examined and total prevalence by helminths was 46,3%. Thirty two species of helminths were recorded, including one species of trematodes, thirteen species of cestodes and eighteen species of nematodes. Three species of nematodes: Heligmosomoides polygyrus, Syphacia frederici, Heligmosomum costellatum and one species of cestodes: Catenotaenia henttoneni were in the dominant helminth group. Low value of helminth species richness in Myodes glareolus is detected and we suggest possible explanation for this pattern.